# Taylor Series Expansion of $f(z)=\frac{1+z}{1-z}$ centered at $i \in\Bbb{C}$

Am I doing this right?

Attempt at solution:

Note that $$\frac{1+z}{1-z}=\frac{1}{1-z}+\frac{z}{1-z}$$. Consider that $$\frac{d}{dz}(\frac{z}{1-z})=\frac{1}{(1-z)^2}=\frac{d}{dz}(\frac{1}{1-z})$$ and the following expansion: \begin{align} \frac{1}{1-z}&=\frac{1}{1-i-z+i}=\frac{1}{1-i-(z-i)}=\frac{1}{(1-i)(1-\frac{z-i}{1-i})}=\frac{1}{1-i}\sum_{k=0}^{\infty}(\frac{z-i}{1-i})^k \end{align} Also, note \begin{align} \int(\frac{z-i}{1-i})^kdz=\frac{1}{(1-i)^k}\int(z-i)^kdz\\ \end{align} \begin{align} \text{Let} \quad u=z-i\quad \text{so} \quad du=dz \quad \text{and}\quad \frac{1}{(1-i)^k}\int(z-i)^kdz=\frac{1}{(1-i)^k}\int u^kdu=\frac{u^{k+1}}{(k+1)(1-i)^k}+C=\frac{(z-i)^{k+1}}{(k+1)(1-i)^k}+C.\quad \text{Thus,}\quad \frac{z}{1-z}=\frac{1}{1-i}\sum_{k=0}^{\infty}\frac{(z-i)^{k+1}}{(k+1)(1-i)^k}\\ \end{align} \begin{align} \text{and we have}\quad \frac{1}{1-z}+\frac{z}{1-z}=\frac{1}{1-i}\Biggl(\sum_{k=0}^{\infty}\biggl(\frac{z-i}{1-i}\biggr)^k + \sum_{k=0}^{\infty}\frac{(z-i)^{k+1}}{(k+1)(1-i)^k}\Biggr) \end{align}

• It might be better to take $$\frac{1+z}{1-z} = -1 + \frac{2}{1-z}$$ Your series for $z/(1-z)$ is wrong. – Robert Israel Oct 25 '18 at 14:08
• Okay thanks, but is my procedure to obtain the expansion of $z/(1-z)$ fine or is it completely wrong? – TheLast Cipher Oct 25 '18 at 14:13

It seems that a straightforward computation, following your first few steps (before the integral appears) gives $$\frac{1+z}{1-z} = i + \sum_{k \geq 0} \frac{(1+i)^{k+1}}{2^k}(z-i)^k$$ (you may want to replace $$(1+i)$$ by $$2^{1/2}e^{i\pi/4}$$ but that doesn't make a huge difference). Are you trying to prove a particular identity?
• Did you follow directly or indirectly? My first few steps only consists of the series for $\frac{1}{1-z}$. How did you manage to slip the other half in? thanks! – TheLast Cipher Oct 25 '18 at 16:13
• In the expression just before "Also, note", I simply multiplied by $(1+z)$, in such a way that $z-i$ also appears explictly, and expressed $1/(1-i)$ as $(1+i)/2$. Simplifying, you get my expression above. – Ϛ . Oct 25 '18 at 16:16